Laser resurfacing of Al–Zn–Mg–Si coatings. (1st December 2016) - Peng, C. T.; Chen, Z.; Liu, Q.; Nolan, D.; Li, H.
Abstract : The feasibility of refinement of Al–Zn–Mg–Si hot dip coatings by diode laser resurfacing has been demonstrated. The microstructure of the laser resurfaced coatings was characterised mainly by transmission electron microscopy and also by scanning electron microscopy. The variance of heat input results in different cooling rates and varying degrees of refinement; that is, the higher the power density, the lower the cooling rate and the larger the secondary dendrite arm spacing of α-Al dendrites. In addition, the inherent variation of chemical composition in coatings also affects the microstructure as well as phase distribution. This laser resurfacing technique has not only reduced the secondary dendrite arm spacing/α-Al dendrites but also changed the solidification path and produce different phases and microstructure in the interdendritic areas.